IMPLEMENTASI AJARAN CATUR WARNA DALAM MERAJUT KEBERSAMAAN GUNA MENCAPAI TUJUAN PEMBANGUNAN NASIONAL - Sugiman (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
In life in the community often appear differences in social status which is often a conflict between the rich, the poor, becoming employees, becoming workers and so on. In the national development arena in Indonesia, every community / citizen has a role to play a role in the implementation of National Development in accordance with their respective competencies, abilities. In the teachings of Catur Warna in the life of the people have blended so that it does not look conspicuous because each color of each has involved each of them, fostering the unity and unity of our country together helping each other, helping each other, supporting each other in the national development is Realizing a prosperous, peaceful, peaceful society based on Pancasila and the 1945 Constitution Catur Warna Conditions in National Development is very strategic regarding the duties and functions of each of us can each of us each. Brahmin has the duty of Mehayu-hayu for peace, interconnected peace, respect for those who love each other, peace-struck people. A Warna Kesatriya has the duty to guarantee the preservation of the nation and the State to improve an honest and clean authoritative Government System for the realization of the goals of National Development. Warna Waisya has a role, regulates and improves the economy in order to lift it, the people and the country. While Warna Sudra has a role and role in national development in order to create a harmonious relationship between helping and completing the work of the Brahmin Color, the Kesatriya leaves of Warna Sudra, so that each other is involved, and in National Development can show Synergy, togetherness about mutual cooperation, a sense of unity and bonding are maintained in harmony with the physical and mental.